(untitled) (Marketing Journal, 2025)
This article analyzes the development trends of the insurance market of Uzbekistan, existing problems in the investment activities of insurance companies and ways to improve them. The need for insurance companies to effectively organize investment activiti es in order to ensure financial stability and increase their competitiveness is substantiated. The article also provides recommendations on diversifying the investment portfolio, risk management and improving regulatory and legal mechanisms based on foreig n experience. Proposals and recommendations 434 developed on the basis of scientific and methodological approaches can serve to increase investment activity in the insurance sector.